Mechanical Properties of Multi-Year Sea Ice. Phase 2. Ice Structure Analysis - Richter-Menge, Jacqueline; Perron, Nancy M (1988)
This report describes the structural analysis of multi-year sea ice samples that were tested in the second phase of a program designed to obtain a comprehensive understanding of the mechanical properties of multi-year sea ice from the Alaskan Beaufort Sea. Each test specimen is classified into one of three major ice texture categories: granular, columnar, or a mixture of columnar and granular ice. The crystallographic orientation, percent columnar ice, and grain size are then evaluated for the granular and/or columnar ice in the sample. Test results are interpreted with respect to these parameters. The overall composition of multi-year ridges is considered, based on the extensive field sampling that was done in the program. The effect of sample orientation on the results is also discussed. Keywords: Sea ice.